2013
DOI: 10.1002/oby.20163
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing healthy gestational weight gain in women at high risk of gestational diabetes: A randomized controlled trial

Abstract: Objective: Optimizing gestational weight gain (GWG) in early pregnancy is of clinical and public health importance, especially in higher risk pregnancies. Design and Methods: In a robustly designed, randomized controlled trial, 228 pregnant women at risk of developing gestational diabetes mellitus (GDM) were allocated to either control (written health information only) or intervention (four-session lifestyle program). All women received standard maternal care. Measures were completed at 12-15 and 26-28 weeks g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
231
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(237 citation statements)
references
References 32 publications
3
231
0
3
Order By: Relevance
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
“…We identified 58 trials published up to June 2015, of which 36 studies (62%) provided individual participant data (IPD),1617343536373839404142434445464748495051525354555657585960616263646566 that accounted for data from 80% of the participants (12 526/15 541); 22 studies (3015 women) did not provide IPD (fig 1). 67686970717273747576777879808182838485868788 A further 45 trials (9945 women)8990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122…”
Section: Resultsmentioning
confidence: 99%
“…In women without GDM, controlling weight gain during pregnancy might limit the incidence of LGA without inducing fetal restriction in those who are overweight/obese. It was recently shown that a low-intensity lifestyle intervention in women at high risk for GDM optimalized healthy GWG, while limiting weight gain was more effective in overweight women [41].…”
Section: Resultsmentioning
confidence: 99%
“…In this trial, lifestyle intervention was more effective than metformin (850 mg twice daily) at reducing T2DM (by 58%; 95% CI [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. However, in a sub-analysis of women with previous pregnancies that were complicated by GDM, metformin was as effective at reducing the incidence of T2DM as lifestyle intervention.…”
Section: Pharmacological Preventionmentioning
confidence: 95%
“…Five other trials have been conducted that have evaluated the benefits of combined lifestyle interventions in pregnant women with obesity and while all have been associated with reduced gestational weight gain, none have improved the risk of developing GDM [46][47][48][49][50] (TABLE 3). However, two of these trials have shown positive effects on materno-fetal outcomes other than improving glycaemia.…”
Section: Women With Obesitymentioning
confidence: 98%
See 1 more Smart Citation